The Impact of Voluntary Recall on the Trust of Loyal and First-Time Consumers in a High Awareness Brand After a Functional Transgression - Valeria L M A Freundt (17541786) (2023)
Brand transgressions might put at risk some of companies’ most important achievements: a high awareness brand and loyal customers’ trust. High awareness brands may suffer from the effects of a functional transgression on customers’ trust and perception regarding an organization’s capacity to keep its promises, as well as the relationship developed with loyal customers. A common outcome of a product functional transgression is government intervention asking for a product recall. The voluntary recall is an alternative to handle brand transgressions, but less common than mandatory product recalls. This paper adds to the literature by theoretically discussing and empirically analyzing how the relationship status of a first-time or loyal customer with a high awareness brand affects consumers’ trust after a functional transgression. Additionally, it examines the moderation effect of response to a functional transgression on the relation between trust’s components—competence, integrity, and benevolence. Through an experimental study 2 (company’s response: passive strategy; voluntary product recall) × 2 (relationship: loyal; first-time) × between-subjects design, the findings indicate that after a high awareness brand transgression, loyal consumers perceive greater competence, integrity, and benevolence in the brand than first-time consumers. When a transgression is followed by a passive strategy in which the transgressor company is aware of a malfunction and decides not to take any action to remediate the situation, loyal consumers have higher integrity and benevolence-based trust perception than first-time consumers. As voluntary recall takes place, loyal and first-time consumers’ perceptions of integrity and benevolence increase, and first-time consumers reach the same levels as loyal consumers, which suggests voluntary product recall is an effective trust recovery strategy for a high awareness brand. Other Information Published in: Corporate Reputation Review License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1057/s41299-023-00164-0